FROM GENDER EQUALITY TO GENDER NEUTRALITY, NEED OR TREND? EXPERIENCES FROM SWEDEN (Heritage, 2024)
Gender neutrality as a concept stems from post-constructivist feminism, emphasizing equality without assumptions and requirements in terms of of gender roles. In its essence, it emphases justice and equal treatment for all. Unlike traditional views of gender and sex, gender neutrality underlines self-awareness and investigation as to how gender can affect behaviors and relationships. The aim of this paper is to present important indicators of gender neutrality in Sweden, which holds a leading position according to the indicators for gender neutral society, and the position of Serbia, which has been undergoing a longstanding process of  implementation of the gender equality policy. The fact of the matter is that progress in these key areas of gender equality improvement in Serbia is happening extremely slowly, which is supported by the fact that only in 59 years could we expect the analyzed parameters to be wholly met through full gender equality. Comparing Serbia with the EU countries according to the Gender Equality Index for 2018, it can be noted that we are 9.4 points behind on average, while we lag behing Sweden by 25.8 points. In this paper we ask important questions that should be addressed by the scientific and professional community, concerning a critical review of the gender-neutral educational future of Serbia, and how we, as a society, are ready for it.
Keywords: Gender neutrality, experiences from Sweden, Serbia and gender equality